Scale invariants of three-dimensional Legendre moments - Ong, , Lee-Yeng; Chong, Chee-Way, Chee-Way; Besar, , Rosli (2006)
Three-dimensional digital images are gaining more attention in pattern recognition field. Mostly literatures, however only focus on theoretical framework of two-dimensional moment invariants, that are only implemented on two-dimensional images. Consequently, it reduces the invariance flexibility to support three-dimensional objects. In this paper we introduce three-dimensional scale invariants of Legendre moments. They are algebraically derived directly from Legendre polynomials. Simulated experiments using three-dimensional binary images are carried out to verify the validity of proposed invariance.